Heat Transfer Simulation and Analysis of Ice and Snow Melting System Using Geothermy by Super-long Flexible Heat Pipes. (May 2017) - Wang, Xiaoyuan; Fan, Hongtu; Zhu, Yuezhao; Zhu, Minzhao
Abstract: An ice and snow melting system (ISMS) using shallow geothermy by super-long flexible heat pipes (SFHPs) was originally proposed. SFHPs were designed with thermally conductive polymer (TCP) intending to reduce cost and make it more conveniently to be fabricated, transported, and installed. Thermal analysis and optimization were carried out assuming ISMS is built in Nanjing city, a typical area with hot summer and cold winter. The results suggest ammonia is optimal for SFHPs concerning the entertainment limit. To kept the pavements free of ice and snow (above 0.5 ̊C), the appropriate interval for condensers arranged is 0.2m. And the recommended dimensions of an SFHP are Φ32×2 mm in diameter and 70m in total length (40m evaporator, 20m condenser) with heat throughput of 1150W at steady state under a typical climatic condition.